Microneedling in the management of melasma: A narrative literature review (Research, Society and Development, 2025)
This narrative review aimed to analyze the available scientific evidence on the use of microneedling in the management of melasma. Melasma is a chronic and recurrent skin hyperpigmentation of multifactorial etiology that mainly affects women of childbearing age and individuals with intermediate to high phototypes, compromising patients’ quality of life. The traditional approach includes topical depigmenting agents and photoprotection, but these do not always lead to satisfactory responses. Microneedling, a technique that produces controlled microperforations in the skin, stimulates skin regeneration, promotes neocollagenesis, and significantly increases skin permeability, allowing greater penetration of depigmenting agents. Among the agents frequently associated with the technique are tranexamic acid, vitamin C, niacinamide, and hyaluronic acid, whose depigmenting, anti-inflammatory, and antioxidant effects are enhanced after microneedling application. The studies analyzed suggest that the technique is safe, well-tolerated, and effective, provided it is performed by trained professionals and with individualized protocols. However, there is a need to standardize the parameters used, such as needle depth, number and interval of sessions, and optimal concentrations of the associated agents. Important contraindications were also highlighted, including the presence of active lesions, healing disorders, and a history of keloids. In summary, microneedling stands out as a promising and complementary therapeutic strategy in the treatment of melasma, especially in cases resistant to conventional approaches.